Revolusi Buku Ajar Bermuatan Teks Multimodal Terintegrasi Media: Kurikulum Merdeka - Sajidah Nur; Nurhadi Nurhadi; Yuni Pratiwi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
One form of implementation of the Independent Curriculum is significant changes to the text content in Indonesian language textbooks. This research aims to describe the presentation of multimodal texts in Indonesian language textbooks which refer to the independent curriculum, namely the Smart Cergas Bahasa Indonesia (CCBI) books for Classes X, XI and XII published by the Ministry of Education and Culture. The research method used to process this research data is a qualitative method. The research results showed that twelve forms of multimodal text were found in the three CCBI books. These twelve form findings show that there are significant differences between Indonesian language textbooks that refer to the Independent Curriculum and those that refer to the 2013 Curriculum. It can be concluded that the content of the twelve forms of multimodal text is one of the innovations and implementations of the independent curriculum. The multimodal text content in CCBI books is a revolution in textbooks that are integrated with learning media.